La falacia intencional: Del New Criticism a la lingüística neurocognitiva - Gil, Jose Maria (2014)
Unintended puns, Freudian slips, conceptual errors, evoke meanings that are independent from (or even incompatible with) the speaker’s intention. But the philosophical and linguistic theories interested in communication and cognition deal exclusively or fundamentally with intentional meaning. I aim at showing that the “intentional fallacy” proposed by Wimsatt and Beardsley (1954), which stated that the author’s intention does not determine interpretation, serves as a solid basis in order to begin to suggest that unintentional meanings are also important in the interpretation of every type of utterance. Relational network theory (Lamb 1999, 2004, 2005, 2006, 2010, 2013) is a neurocognitive approach that can handle unintentional meanings by means of a method that could be compared to the method suggested by representative authors of New Criticismand without disregarding the importance of unintentional meanings.